Swedish Parents’ Perspectives of Belonging in Early Years Education - Karlsudd, Peter (Frontiers in Education, 2022)
This article presents the results and experiences on parents’ perspectives of belonging in early years education. The study aimed to investigate how the parents assess the fulfilment of the inclusion goals that apply to the Swedish preschool activities. Another aim was to learn about the parents’ perspectives on factors and pedagogical approaches that promote diversity and belonging. The study involves the answers from 454 parents/guardians of preschool pupils. When the parents were asked directly if their children were excluded by others in the group, 14% stated it was true. The present study tried to find factors and connections to strengthen the preschool’s inclusive working methods. One way to have children become more included in the group is to get the parents more involved and familiar with activities and for the staff to convey the goals that apply to activities.